Investigation of the pharmacological effect of tokishakuyakusan by global transcriptional analysis in humans - Hayasaki, Tomoyuki; Ikeda, Tatsuhiko; Kanaya, Shigehiko; Katoh, Akira; Hanawa, Toshihiko; Sakurai, Masatomo; Oikawa, Tetsuro; Shojo, Masayuki; Ninomiya, Yuka (Journal of Traditional Medicines, 2010)
The pharmacological effect of tokishakuyakusan was assessed by human transcriptome analysis. Tokishakuyakusan was administrated to 24 female participants, who had complained of feeling cold, edema and gynecological symptoms, for 4 weeks and the pharmacological effects were analyzed. Global transcription was assessed by cDNA microarray using RNA from nucleated cells in the subjects' peripheral blood. Overall, 953 genes were up-regulated and 1,067 were down-regulated with significant differences (p-value of Student's t-test <0.05, with FDR <0.05). A human Gene Ontology (GO) database and the software tool "KNApSAcK human gene classifier", which enables the comparison of the ratio of genes corresponding to functional-categories in an arbitrary gene set to that of the entire human gene set, were developed to understand significant transients in gene expression. The transients were functionally categorized into protein synthesis, transport facilitation, protein fate, transcription, cell cycle and DNA processing, cell fate, transcription, and cellular communication/signal transduction mechanism, with significance (p-value <0.01) determined by a z-test for comparing two proportions using KNApSAcK. Genes related to estrogen, GABAergic signaling, angiotensin and tumors were found to be significant categories.